2017
DOI: 10.1021/acs.est.7b00827
|View full text |Cite
|
Sign up to set email alerts
|

Does Waterborne Exposure Explain Effects Caused by Neonicotinoid-Contaminated Plant Material in Aquatic Systems?

Abstract: Neonicotinoids are increasingly applied on trees as protection measure against insect pests. Consequently, neonicotinoids are inevitably transferred into aquatic environments either via spray drift or surface runoff or (due to neonicotinoids' systemic nature) via senescent leaves. There particularly leaf-shredding invertebrates may be exposed to neonicotinoids through both the water phase and the consumption of contaminated leaves. In 7 day bioassays (n = 30), we examined ecotoxicological differences between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 56 publications
2
25
0
2
Order By: Relevance
“…However, such differences tend to be species specific. For example, recent studies have shown that the amphipod Gammarus fossarum is more susceptible than the caddisfly Chaetopteryx villosa when exposed to three neonicotinoids (imidacloprid, thiacloprid, and acetamiprid), either alone or in mixtures (Englert et al 2017). Furthermore, the same study found that combined exposure of these shredder species to neonicotinoid residues in water and in food (tree leaves) had more negative impacts on their survival than direct exposure to contaminated water alone.…”
Section: Effects On Aquatic Invertebratesmentioning
confidence: 97%
See 2 more Smart Citations
“…However, such differences tend to be species specific. For example, recent studies have shown that the amphipod Gammarus fossarum is more susceptible than the caddisfly Chaetopteryx villosa when exposed to three neonicotinoids (imidacloprid, thiacloprid, and acetamiprid), either alone or in mixtures (Englert et al 2017). Furthermore, the same study found that combined exposure of these shredder species to neonicotinoid residues in water and in food (tree leaves) had more negative impacts on their survival than direct exposure to contaminated water alone.…”
Section: Effects On Aquatic Invertebratesmentioning
confidence: 97%
“…Eventually, soil residues move into the aquatic ecosystems, either by percolation and leaching through the soil profile (de Perre et al 2015;Wettstein et al 2016) or in surface runoff after rainfall and storms (Chrétien et al 2017). Foliar sprays and drenches applied to orchard trees also contribute to the contamination of waterways (Englert et al 2017;Kreutzweiser et al 2008b). There is sufficient evidence to date to state that water borne residues of neonicotinoids and fipronil are currently impacting on aquatic ecosystems, as shown in the recent review by Sánchez-Bayo et al (2016).…”
Section: Impacts On Aquatic Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, reduced fungal population on leaf litter has been shown to be associated with reduced amphipod growth, potentially attributable to reduced nutrition (Elskus et al ). These feeding effects could be exacerbated by coexposure to imidacloprid, which has also been shown to reduce macroinvertebrate feeding on leaf matter (Kreutzweiser et al ; Nyman et al ; Englert et al ). In this context of sublethal effects, it would be valuable to repeat the present study for the most sensitive species (e.g., N. triangulifer ) for a chronic exposure duration.…”
Section: Discussionmentioning
confidence: 99%
“…Residue levels significantly depended on the dose and compound applied, as well as the physiological parameters of the trees. Englert et al (2017b) reviewed the literature on foliar residues of neonicotinoids and found that they ranged between 1000 and 6000 ppb for soil and trunk application in deciduous trees and 80 and 300 ppb for soil and trunk applications of evergreen trees.…”
Section: Water and Sedimentsmentioning
confidence: 99%